Hippocampal Administration of Levothyroxine Impairs Contextual Fear Memory Consolidation in Rats - Yu, Dafu; Zhou, Heng; Zou, Lin; Jiang, Yong; Wu, Xiaoqun; Jiang, Lizhu; Zhou, Qixin; Yang, Yuexiong; Xu, Lin; Mao, Rongrong (Frontiers in Cellular Neuroscience, 2017)
Thyroid hormone receptors are highly distributed in the hippocampus, which plays vital role in memory processes. However, how thyroid hormones (THs) are involved in the different stages of memory process is little known. Herein, we used hippocampus dependent contextual fear conditioning to address the effects of hippocampal THs on the different stages of fear memory. Firstly, we found that a single systemic levothyroxine (LT4) administration increased the level of free triiodothyronine (FT3) and free tetraiodothyroxine (FT4) not only in serum but also in hippocampus. In addition, a single systemic LT4 administration immediately after fear conditioning significantly impaired fear memory. These results indicated the important role of hippocampal THs in fear memory process. To further confirm the effects of hippocampal THs on the different stages of fear memory, LT4 (0.4 μg/μl, 1 μl/side) was injected bilaterally into hippocampus. Rats given LT4 into hippocampus before training or tests had no effect on the acquisition or retrieval of fear memory, however rats given LT4 into hippocampus either immediately or 2 hours after training showed being significantly impaired fear memory, which demonstrated LT4 administration into hippocampus impairs the consolidation but has no effect on the acquisition and retrieval of fear memory. Furthermore, hippocampal injection of LT4 did not affect rats’ locomotor activity, thigmotaxis and THs level in prefrontal cortex and serum. These findings may have important implications for understanding mechanisms underlying contribution of THs to memory disorders.